2021
DOI: 10.1007/s40257-021-00603-w
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Treatment Algorithms for Moderate-to-Severe Psoriasis with Comorbid Conditions and Special Populations: A Review

Abstract: The emergence of data from clinical trials of biologics, the approval of new biologics, and our improved understanding of psoriasis pathogenesis have increased the therapeutic possibilities for the treatment of moderate-to-severe psoriasis. Biologics currently approved for the treatment of psoriasis include tumor necrosis factor inhibitors, interleukin (IL)-17 inhibitors, ustekinumab (an IL-12/23 inhibitor), and IL-23 inhibitors. Data from clinical trials and studies of the safety and efficacy of biologics pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 191 publications
(79 reference statements)
3
64
0
9
Order By: Relevance
“…Elevated IL-17 levels were accompanied by a corresponding increase in CD4+ Th17 cell count in end-stage congestive HF (NYHA class IV) compared to the control group and patients with NYHA class I HF [ 90 ]. Three anti-IL-17 agents are currently available and recommended to treat psoriasis in patients with concomitant congestive HF [ 91 ]. Secukinumab and ixekizumab directly bind to IL-17A, whereas brodalumab occupies the IL-17 receptor A, preventing IL-17A from activating the receptor—all antagonizing the IL-17A signaling pathway [ 92 ].…”
Section: Targeting Inflammatory Cytokines In Heart Failurementioning
confidence: 99%
“…Elevated IL-17 levels were accompanied by a corresponding increase in CD4+ Th17 cell count in end-stage congestive HF (NYHA class IV) compared to the control group and patients with NYHA class I HF [ 90 ]. Three anti-IL-17 agents are currently available and recommended to treat psoriasis in patients with concomitant congestive HF [ 91 ]. Secukinumab and ixekizumab directly bind to IL-17A, whereas brodalumab occupies the IL-17 receptor A, preventing IL-17A from activating the receptor—all antagonizing the IL-17A signaling pathway [ 92 ].…”
Section: Targeting Inflammatory Cytokines In Heart Failurementioning
confidence: 99%
“…Other studies have shown that in presence of severe viral symptoms with high fever develop, the discontinuation of IL-17 inhibitors should be considered [ 120 , 121 ]. On the other hand, although IL-17 has an important role in mucosal immunity, preliminary studies by Wan et al [ 122 ] and Tathiparthi et al [ 123 ] did not prove any increased risk of either severe infection or negative outcome. Moreover, apremilast was shown having a good safety profile in COVID-19 affected patients, in fact, it does not favor either infection or cytokine storm, and it does not increase the risk of pulmonary fibrosis [ 124 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, secukinumab was found to significantly reduce work impairment and psoriasis-associated indirect costs compared with ustekinumab and etanercept [ 35 ]. Furthermore, secukinumab has a more favorable safety profile and fewer contraindications than adalimumab [ 36 , 37 ]; for example, secukinumab carries lower risk of serious infections, demyelinating diseases, and reactivation of latent tuberculosis or hepatitis B, making it a preferred choice in some patients.…”
Section: Discussionmentioning
confidence: 99%